ANALISIS NILAI SOSIAL-RELIGIUS DALAM TRADISI BERSIH DESA DI DESA SONOAGENG KABUPATEN NGANJUK - Rina, Rina; Wahyu, Bagus (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
This study aims to describe the role of village clean traditions, as well as describe the socio-religious values ​​in village clean traditions. The formulation of the problems in this research includes 1.) How is the role of village clean traditions in the village of Sonoageng, Nganjuk district? 2.) How to realize socio-religious values ​​in the village clean tradition in Sonoageng village, Nganjuk district? This research uses a qualitative approach, data collection techniques using literature. The research findings show that clean village traditions in the Javanese perspective are considered as a form of community gratitude to the Almighty for the abundance of sustenance that has been given. This research can be concluded that social values ​​that can be used as a guide in everyday behavior.